2017
DOI: 10.1038/s41598-017-04186-7
|View full text |Cite
|
Sign up to set email alerts
|

IFN-λ4 potently blocks IFN-α signalling by ISG15 and USP18 in hepatitis C virus infection

Abstract: Genetic polymorphisms in IFNL4 have been shown to predict responses to IFN-α-based therapy in hepatitis C virus (HCV)-infected patients. The IFNL4-ΔG genotype, which encodes functional IFN-λ4 protein, is associated with a poor treatment response. In the present study, we investigated the induction and biological effects of IFN-λ4 in HCV-infected hepatocytes and their association with responsiveness to IFN-α. We also studied the effects of direct-acting antiviral (DAA) treatment on IFN-λ4 expression and IFN-α r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…5A). IFNλ4 stimulation reportedly leads to the assembly of the ISGF3 transcription factor complex, which consists of phospho-STAT1, phospho-STAT2, and IRF9 and induces the expression of ISG15 [27], which is critical for anti-viral activity [28]. We showed that the M1, M3, and M7 IFNλ4 variants also induced the expression of ISG15 and inhibited HCV replication in HCVinfected Huh-7.5 cells ( Fig.…”
Section: Receptor Binding Affinity and Biological Activity Of Ifnλ4 Vmentioning
confidence: 65%
See 2 more Smart Citations
“…5A). IFNλ4 stimulation reportedly leads to the assembly of the ISGF3 transcription factor complex, which consists of phospho-STAT1, phospho-STAT2, and IRF9 and induces the expression of ISG15 [27], which is critical for anti-viral activity [28]. We showed that the M1, M3, and M7 IFNλ4 variants also induced the expression of ISG15 and inhibited HCV replication in HCVinfected Huh-7.5 cells ( Fig.…”
Section: Receptor Binding Affinity and Biological Activity Of Ifnλ4 Vmentioning
confidence: 65%
“…In this regard, a recent study demonstrated that IFNλs can suppress influenza virus without the inflammatory side effects of IFNα [44]. However, it was previously shown that the expression of functional IFNλ4 is associated with unresponsiveness to IFNα treatment among HCV-infected patients [9], and a subsequent study showed that long-term exposure to IFNλ4 leads to cellular unresponsiveness to IFNα treatment by upregulation of USP18 or SOCS1 [27,29], indicating that IFNλ4 treatment may be detrimental to virus-infected patients. On the other hand, our result shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies confirmed the inverse correlation with hepatic ISG set‐point levels and outcome of IFN therapy and showed cell‐type–specific differences in ISG expression . Induction of type III IFNs is the predominant antiviral pathway and driver of ISG induction, which render hepatocytes refractory to further type I IFN action, conceptually supported by the observation that blocking type III IFN enhances the antiviral activity of exogenous IFN‐α …”
mentioning
confidence: 79%
“…Once sufficient viral proteins have accumulated in the cytosol, HCV uses its multifunctional NS3/4A protease, essential for HCV replication, to cleave MAVS and ablate RIG‐I–mediated innate immune signaling . Moreover, not all ISGs benefit the host, and several ISGs (including ISG15 and ubiquitin‐specific peptidase 18 [USP‐18]) have been reported to have proviral properties …”
mentioning
confidence: 99%